2019
DOI: 10.3389/fphys.2019.00922
|View full text |Cite
|
Sign up to set email alerts
|

Early Postnatal Heart Rate Variability in Healthy Newborn Infants

Abstract: Background Despite the increasing interest in fetal and neonatal heart rate variability (HRV) analysis and its potential use as a tool for early disease stratification, no studies have previously described the normal trends of HRV in healthy babies during the first hours of postnatal life. Methods We prospectively recruited 150 healthy babies from the postnatal ward and continuously recorded their electrocardiogram during the first 24 h after birth. Babies were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 32 publications
(39 reference statements)
2
34
0
1
Order By: Relevance
“…In the last 40 years, heart rate variability (HRV) has emerged as a reliable and non-invasive measure to monitor preterm and term newborns (Task Force of the European Society of Cardiology the North American Society of Pacing Electrophysiology, 1996). HRV evaluates the heart rate (HR) fluctuation-the variability of the time intervals between successive heartbeats-, and during the years, more and more techniques have appeared to improve its analysis, from which several metrics can be extracted ( Table 1; Bravi et al, 2011;Thiriez et al, 2015;Javorka et al, 2017;Oliveira et al, 2019b;Patural et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the last 40 years, heart rate variability (HRV) has emerged as a reliable and non-invasive measure to monitor preterm and term newborns (Task Force of the European Society of Cardiology the North American Society of Pacing Electrophysiology, 1996). HRV evaluates the heart rate (HR) fluctuation-the variability of the time intervals between successive heartbeats-, and during the years, more and more techniques have appeared to improve its analysis, from which several metrics can be extracted ( Table 1; Bravi et al, 2011;Thiriez et al, 2015;Javorka et al, 2017;Oliveira et al, 2019b;Patural et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that HRV correlates with the newborn's stress and stress-related behaviors (Gardner et al, 2018;Hashiguchi et al, 2020), and that it could predict the baby's overall wellbeing and future neurological development. HRV could also accurately identify short-and long-term complications, such as the risk of sepsis (Javorka et al, 2017;Oliveira et al, 2019b;Kumar et al, 2020). HRV was also able to reveal the impact of prenatal stress on fetal brain development (Frasch et al, 2007;Lobmaier et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations